Tear and serum eosinophil cationic protein levels in seasonal allergic conjunctivitis - TOKER, AYŞE EBRU (SAGE PUBLICATIONS LTD, 2003)
PURPOSE. Eosinophil cationic protein (ECP) levels in tear fluid and sera of patients with seasonal allergic conjunctivitis (SAC) were measured to assess local and systemic eosinophilic activity in SAC. The correlation between ECP levels and disease activity was evaluated. METHODS. Tears and sera were collected from 21 patients with SAC and 13 healthy control subjects. ECP levels in tears and sera were measured before and 4 weeks after treatment with 0.1% lodoxamide eyedrops. Clinical signs and symptoms of SAC were scored and the correlation of ECP levels with the clinical scores was evaluated. RESULTS. Tear and serum levels of ECP were significantly increased (p=0.01, p=0.02, respectively) in patients with SAC compared with the control subjects, but ECP levels were not correlated with the severity of the disease. Following treatment with topical 0.1% lodoxamide eyedrops, the mean level of ECP in tears decreased significantly (p=0.02), whereas no significant change was observed in serum ECP levels. Furthermore, a significant decrease in clinical signs and symptoms scores was found after treatment (both p<0.0001). CONCLUSIONS. Increased serum and tear ECP levels in patients with SAC confirms that both local and systemic eosinophil activation occurs in SAC, However, clinical signs and symptoms of SAC were not found to be correlated with the degree of eosinophilic activity. Thus ECP does not seem to have an important role in clinical manifestations of SAC.
Keywords: seasonal allergic conjunctivitis; eosinophil cationic protein; lodoxamide; MAJOR BASIC-PROTEIN; VERNAL KERATOCONJUNCTIVITIS; INFLAMMATORY MEDIATORS; GRANULE PROTEINS; OCULAR ALLERGY; LODOXAMIDE; RHINITIS; ASTHMA; CELLS; IMMUNOTHERAPY